Association between proximity to industrial chemical installations and cancer mortality in Spain. (May 2020) - Ayuso-Álvarez, Ana; García-Pérez, Javier; Triviño-Juárez, José-Matías; Larrinaga-Torrontegui, Unai; González-Sánchez, Mario; Ramis, Rebeca; Boldo, Elena; López-Abente, Gonzalo; Galán, Iñaki; Fernández-Navarro, Pablo
Abstract: It is likely that pollution from chemical facilities will affect the health of any exposed population; however, the majority of scientific evidence available has focused on occupational exposure rather than environmental. Consequently, this study assessed whether there could have been an excess of cancer-related mortality associated with environmental exposure to pollution from chemical installations – for populations residing in municipalities in the vicinity of chemical industries. To this end, we designed an ecological study which assessed municipal mortality due to 32 types of cancer in the period from 1999 to 2008. The exposure to pollution was estimated using distance from the facilities to the centroid of the municipality as a proxy for exposure. In order to assess any increased cancer mortality risk in municipalities potentially exposed to chemical facilities pollution (situated at a distance of ≤5 km from a chemical installation), we employed Bayesian Hierarchical Poisson Regression Models. This included two Bayesian inference methods: Integrated Nested Laplace Approximations (INLA) and Markov Chain Monte Carlo (MCMC, for validation). The reference category consisted of municipalities beyond the 5 km limit. We found higher mortality risk (relative risk, RR; estimated by INLA, 95% credible interval, 95%CrI) for both sexes for colorectal (RR, 1.09; 95%CrI, 1.05–1.15), gallbladder (1.14; 1.03–1.27), and ovarian cancers (1.10; 1.02–1.20) associated with organic chemical installations. Notably, pleural cancer (2.27; 1.49–3.41) in both sexes was related to fertilizer facilities. Associations were found for women, specifically for ovarian (1.11; 1.01–1.22) and breast cancers (1.06; 1.00–1.13) in the proximity of explosives/pyrotechnics installations; increased breast cancer mortality risk (1.10; 1.03–1.18) was associated with proximity to inorganic chemical installations. The results suggest that environmental exposure to pollutants from some types of chemical facilities may be associated with increased mortality from several different types of cancer. Graphical abstract: Image 1 Highlights: Excess risk of cancer mortality was found in the vicinity of chemical facilities. Colorectal, gallbladder and ovary cancer mortality related to organic chemical facilities. Ovarian and breast cancer mortality related to explosives/pyrotechnics facilities. Excess of pleural cancer mortality in municipalities close to fertilizer facilities. Excess of Breast cancer mortality in municipalities close to inorganic chemical facilities. Abstract : Environmental exposure to pollutants from some chemical facilities, measured by proximity, may be associated with increased mortality risk from different types of cancer.